Research on multi-parameter correction of vibration system based on genetic Algorithm. Issue 1 (January 2021) - He, Shihao; Zhou, Cheng; Yu, Cungui
Abstract: In order to solve the problem of fast solving the vibration system under complex excitation, a co-simulation method based on the mathematical simulation model and the multi-parameter correction of the vibration system is proposed. According to the dynamics theory of multi-body systems, the dynamic equations of the system are derived. Runge-Kutta method and MATLAB software are used to solve the dynamic equations. Compared with ADAMS multi-body simulation, the accuracy and efficiency of the dynamic equations are proved. The vibration test is carried out to obtain the acceleration data required to construct the multi-objective function. Optimal solution of modified parameters is obtained by multi-objective genetic algorithm. Finally, the vibration test bench system was used to verify the feasibility of the multi-parameter correction method. The results show that the error of the modified objective function of the constructed vibration test bench system is greatly reduced, which verifies the effectiveness of the multi-parameter correction method.